Proceedings of the 1st International Conference on Advanced Multidisciplinary Research (ICAMR 2018) 2019
DOI: 10.2991/icamr-18.2019.72
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 5E Learning Cycle Model Assisted with Mind Mapping on Students’ Science Process Skills and Academic Achievement in the Respiratory System Subject Matter

Abstract: The this study aimed to determine the effect of the 5E Learning Cycle model assisted with mind mapping on Science Process Skills (SPS) and Students' Academic Achievement of The Respiratory System subject matter. This type of research is Quasi-Experimental, using the Nonequivalent Pretest-Posttest design. The study population was 8th-grade students of State of junior high school (SMP 3 Watampone) as many as 8 classes with 218 students in the 2017/2018 school year. The sampling method was purposive sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In other studies focused on the 5E learning model applications in science courses, also a significant increase in students' basic process skills were observed (Ercan Özaydın, 2010;Öztürk, 2013;Sole & Wilujeng, 2013). Since the basic process skills contribute significantly to the understanding of science subjects with the 5E learning model (Akar, 2005), it is critical to employ the model that requires students to actively observe and conduct research to build concepts in their minds (Ramalawati, Adam, Rusli & Mun'in, 2018). This helps students to reach and prove real knowledge thorough scientific activities.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…In other studies focused on the 5E learning model applications in science courses, also a significant increase in students' basic process skills were observed (Ercan Özaydın, 2010;Öztürk, 2013;Sole & Wilujeng, 2013). Since the basic process skills contribute significantly to the understanding of science subjects with the 5E learning model (Akar, 2005), it is critical to employ the model that requires students to actively observe and conduct research to build concepts in their minds (Ramalawati, Adam, Rusli & Mun'in, 2018). This helps students to reach and prove real knowledge thorough scientific activities.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Studies conducted on the effect of 5E instructional strategy reported a glaring difference in the learning outcome of learners. Their results were in favor of students who were tutored using the 5Es model as against students tutored using the conventional method (Ramlawati, Aqil, Adam, & Mun'im, 2019;Umahaba, 2018). For instance, the 5E learning model improves the cognition effect of students (Koyunlu & Dökme, 2020), problemsolving ability (Kalantarnia et al, 2020), higher-order thinking/cognitive skills (Ramlee, Rosli, & Saleh, 2019), creativeness (Conradty et al, 2020;Güven, Kozcu Cakir, Sulun, Cetin, & Guven, 2020;Kalantarnia et al, 2020) and curiosity (Gillies & Rafter, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%